Pengaruh Reward Ekstrinsik & Intrinsik Terhadap Kinerja Dengan Kepuasan Kerja Sebagai Variabel Intervening - Syahril, Rizky Ramadhan; Nurbiyati, Titik (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2016)
This study is concerned with how the effect of extrinsic and intrinsic reward to performance and job satisfaction as an intervening variable. The purpose of this study was to determine the effect of reward extrinsic and intrinsic job satisfaction and performance either partially or simultaneously, determine the effect of job satisfaction on performance as well as find out more where the effect directly reward extrinsic and intrinsic to the performance of employees with indirect influence reward extrinsic and intrinsic rewards to employee performance. Respondents of this study consist of 100 employees. The employed data of this study are primary data. The data is collected by distributing questionnaires to respondents. The data is analyzed by regression analysis and path.The results show that partially or simultaneously reward extrinsic and intrinsic are significant positive effect on job satisfaction and performance. There are positive and significant impact on job satisfaction toward employees performance as well as an indirect effect (reward extrinsic and intrinsic to the performance of employees through job satisfaction) greater than a direct effect (extrinsic and intrinsic reward to employees performance). Keywords: Reward extrinsic, intrinsic rewards, job satisfaction, Employee Performance